Centro de Investigación para la Adaptación al Cambio Climático Plan Parcial Biogénesis Urbana Bogotá D.C. - Colombia (2018)
The development of a project of regional scale in the town of Suba comes as part of an analysis of the problems, opportunities and potentials of the area, outlined from different social, environmental, functional and institutional variables that allow the construction of the Innovation Center project and Research for Adaptation to Climate Change. This analysis links the communities, their development prospects, their relationship with the urban - natural environment and the educational and training needs. We study the social processes that have determined the illegal development of the Tibabuyes neighborhood of the Suba locality, generating a habitability with low indicators of quality of life and relationship with nature, and how, through architecture and urbanism, it can be faced and solve these problems, allowing the inhabitants to enjoy a primordial welfare for human development.